The spectrum and clinical outcome of civilian cerebral gunshot wounds at a major trauma centre in South Africa - Kong, Victor (My University, 2021)
Introduction: Cerebral gunshot wounds (GSWs) are highly lethal injuries and are common in South Africa. Literature focusing on the injury spectrum and clinical outcome in the specific context of the developing world setting in South Africa is limited. Materials and Methods: This Doctor of Medicine (MD) thesis is based on a series of retrospective studies undertaken at the Pietermaritzburg Metropolitan Trauma Service (PMTS), Pietermaritzburg, South Africa. The regional trauma registry was used as the basis for the studies and was reviewed over a five-year period (January 2010 to December 2014). The thesis comprises six published papers in peer-reviewed journals which examine different aspects of cerebral GSWs within the South African context. Results: A total of 102 patients were included in these studies in which 92% were male, with a mean age of 29 years. In Chapter 1 (Article 1), we demonstrate that in our setting, cerebral GSWs occur primarily in young males who are predominantly victims of interpersonal violence involving low-velocity firearms, with self-harm and accidental injuries being uncommon. The overall mortality was high. Chapter 2 (Article 2) demonstrates that rural patients have disproportionally higher mortality compared with their urban counterparts, likely related to prolonged transfer time to definitive care. Chapter 3 (Article 3) demonstrates that for those patients who were transferred to our trauma centre, the Baragwanath mortality-prediction score accurately predicted non-survivors and was directly applicable to our patient cohort. Chapter 4 (Article 4) highlights that the Maritzburg score, based on the presence of visible brain matter and a GCS motor score < 5 on admission, allows simpler and more accurate identification of non-survivors. Chapter 5 (Article 5) demonstrates that a raised serum-lactate level on presentation was closely correlated to adverse outcome and is an independent predictor of in-hospital mortality while Chapter 6 (Article 6) demonstrates that patients with isolated cerebral GSWs were highly unlikely to sustain concomitant cervical spine injury and therefore routine cervical spine immobilisation is unnecessary. Conclusions: Cerebral GSWs are associated with high mortality, with rural patients having disproportionately higher mortality than their urban counterparts. Relevant prediction scores based on simple clinical parameters that are readily available in the resuscitation room, as well as a raised serum-lactate level are accurate in predicting non-survivors in our resource-constrained environment. Concomitant cervical spine injury in isolated cerebral GSW is extremely rare and routine cervical spine immobilisation is unnecessary. Efforts should therefore rather be directed at management strategies aiming to prevent secondary brain injury in order to optimise clinical outcome.
A thesis submitted to the Department of Surgery, Faculty of Health Sciences, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Medicine (MD)